2021
DOI: 10.7150/ijbs.63390
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Mediated Secretion of HLA-E by Trophoblasts Maintains Pregnancy by Regulating the Metabolism of Decidual NK Cells

Abstract: Extracellular vesicles derived from trophoblasts (T-EVs) play an important role in pregnancy, but the mechanism is not entirely clear. In this study, we found that HLA-E, which is mostly confined to the cytoplasm of trophoblast cells, was secreted by T-EVs. The level of HLA-E in T-EVs from unexplained recurrent spontaneous abortion (URSA) patients was lower than that in normal pregnancy (NP) and RSA patients who had an abnormal embryo karyotype (AK-RSA). T-EVs promoted secretion of IFN-γ and VEGFα by decidual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…48 Further to this, this in vivo study demonstrated that the inhibition of T-EVs caused more embryo absorption, coupled with a significant reduction in INFγ and VEGFα in dNK cells. 48 As a result, these studies suggested that glucose-driven glycolysis might be required for the activation of dNK cells, but driving forces of glycolysis in the microenvironment might also be involved in the balance between cytotoxic and regulatory functions. However, further studies are still warranted.…”
Section: Carbohydrate Metabolismmentioning
confidence: 55%
See 3 more Smart Citations
“…48 Further to this, this in vivo study demonstrated that the inhibition of T-EVs caused more embryo absorption, coupled with a significant reduction in INFγ and VEGFα in dNK cells. 48 As a result, these studies suggested that glucose-driven glycolysis might be required for the activation of dNK cells, but driving forces of glycolysis in the microenvironment might also be involved in the balance between cytotoxic and regulatory functions. However, further studies are still warranted.…”
Section: Carbohydrate Metabolismmentioning
confidence: 55%
“…48 As shown in that study, it was also observed that the level of HLA-E in the T-EVs from women with URPL was significantly 6) Maternal obesity leads to a significant reduction in dNK cell numbers but increased TNFα production and impaired uterine artery remodeling or placental development lower than in women with normal pregnancies and pregnancy loss caused by an abnormal embryo karyotype. 48 Further to this, this in vivo study demonstrated that the inhibition of T-EVs caused more embryo absorption, coupled with a significant reduction in INFγ and VEGFα in dNK cells. 48 As a result, these studies suggested that glucose-driven glycolysis might be required for the activation of dNK cells, but driving forces of glycolysis in the microenvironment might also be involved in the balance between cytotoxic and regulatory functions.…”
Section: Carbohydrate Metabolismmentioning
confidence: 64%
See 2 more Smart Citations
“…Consequently, dNK cellular metabolism and functions are impaired, which might participate in the pathogenesis of RPL. Indeed, recent studies have revealed that glycolysis disturbance occurs at the decidua of RPL, and attenuated ECAR and OCR in RPL dNK compared with healthy controls has also been reported ( 45 , 46 ). In this study, protein levels of HK-II and LDHA were found to be altered, and a decreased mTORC1 activity was observed by Western blot in the RPL decidual samples analyzed.…”
Section: Discussionmentioning
confidence: 97%